Genetic Testing in Patients with Hypertrophic Cardiomyopathy - Bonaventura, Jiri; Polakova, Eva; Vejtasova, Veronika; Veselka, Josef (International journal of molecular sciences, 2021)
Hypertrophic cardiomyopathy (HCM) is a common inherited heart disease with an estimated prevalence of up to 1 in 200 individuals. In the majority of cases, HCM is considered a Mendelian disease, with mainly autosomal dominant inheritance. Most pathogenic variants are usually detected in genes for sarcomeric proteins. Nowadays, the genetic basis of HCM is believed to be rather complex. Thousands of mutations in more than 60 genes have been described in association with HCM. Nevertheless, screening large numbers of genes results in the identification of many genetic variants of uncertain significance and makes the interpretation of the results difficult. Patients lacking a pathogenic variant are now believed to have non-Mendelian HCM and probably have a better prognosis than patients with sarcomeric pathogenic mutations. Identifying the genetic basis of HCM creates remarkable opportunities to understand how the disease develops, and by extension, how to disrupt the disease progression in the future. The aim of this review is to discuss the brief history and recent advances in the genetics of HCM and the application of molecular genetic testing into common clinical practice.
Keywords: Muscle Proteins; svalové proteiny; variants of uncertain significance; genetické testování; genetics; next-generation sequencing; hypertrophic cardiomyopathy; mutace; sarkomery; Mutation; Humans; Cardiomyopathy, Hypertrophic; Genetic Testing; hypertrofická kardiomyopatie; pathogenic mutations; lidé; molecular genetic testing; Sarcomeres